ANALISIS FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA PADA PERUSAHAAN (Survey Pada Perusahaan Perdagangan, Jasa dan Investasi di BEI 2013) - Satria Muharofiq; Desmiyawati -; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to provide a general overview of trends in practice income smoothing and the factors that influence it. And measure whether the company size, level of probability, Financial Leverage factor, Net Profit Margin and Varian Value Equity income smoothing effect on the occurrence of the companies listed in the Indonesia Stock Exchange.This study using purposive sampling technique in which this study took company data trade, services and investments are listed on the Stock Exchange in the period 2013. The population of this research the population were 113 companies with a selected sample of the sample is based on research criteria Inroads as many as 51 companies sampled. The analysis method used in this research is descriptive method, by doing alalisis partially and simultaneously (multiple linear regression analysis with SPSS version 17.0).the testing that has been done from the result, simultaneous regression test (TestF) showed that all independent variables in this study did not have a significant effect on the variable income smoothing. Partial regression test (t test) showed that each variable testing indicate that all of these variables did not have a significant effect on income smoothing is visible from t value of all the independent variables is smaller than t table. And also the significant value of all these variables is greater than the probability value is equal to 0.05 so that it can be concluded that the independent variables in this study had no effect on the dependent variable.Keywords: Company size, Profitability, Financial Leverage, Net Profit Margin and Variance Value of shares.